World commodity prices 1996 - 1998: Report presented to the AIECE spring meeting, Venice, May 5 - 8, 1997 - Jörg-Volker Schrader (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
World commodity prices increased in 1996 on aggregate by 7 percent. However, taking yearly averages, this was the result of heterogeneous developments: increasing oil prices, which have a dominant weight, and falling prices for industrial raw materials and food and beverages. Forecasts for 1997 and 1998 point in the opposite direction: oil prices are expected to fall slightly whereas industrial raw material prices are likely to increase, a process which already began at the end of 1996 and will level off through 1998. Prices for food and beverages will decline slightly after a pronounced increase during the first months of 1997.
Keywords: 330; Rohstoffpreis; Prognose; Welt